Preparation method of geopolymer composite material based on modified fibers
By combining the surface modification of basalt fibers or polyformaldehyde fibers with alkali exciter, high-strength and crack-resistant geopolymer composites are prepared, which solves the brittleness of geopolymer materials, improves the toughness and crack-resistant properties of the material, and at the same time realizes the high-value utilization of industrial waste slag.
Patent Information
- Application Number
- CN202510636086.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-01
AI Technical Summary
Geopolymer materials show high brittleness and low toughness in actual engineering. Existing fiber toughening methods such as glass fiber, steel fiber, polypropylene fiber and basalt fiber are easily corroded in alkaline environments or have weak interface binding forces, resulting in reduced mechanical properties and toughness.
Basalt fibers or polyformaldehyde fibers are pretreated, and the fibers are surface roughened and functionalized modified by polyvinyl alcohol modified wetting agents and functionalized modified wetting agents. Combined with alkali triggers and expansion agents, functionalized modified fibers are prepared to form high-strength, crack-resistant polymer composites with industrial solid waste slag coal gangue and slag.
It significantly improves the mechanical locking and interface bonding between fiber and geopolymer matrix, enhances the toughness and crack resistance of the material, promotes the high-value utilization of industrial solid waste slag, reduces carbon emissions, and expands the application range of geopolymer materials.
Smart Images

Figure CN120398471A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of engineering materials, and particularly relates to a preparation method of a geopolymer composite material based on modified fibers. Background Art
[0002] Geopolymers are mostly made from industrial solid waste and are three-dimensional network-structured inorganic polymers formed by alkali activation, consisting of AlO4 and SiO4 tetrahedral structural units. Compared with Portland cement, geopolymers have better mechanical properties, low pollution, sustainability, etc. However, in actual engineering, geopolymers often exhibit disadvantages such as high brittleness and low toughness, and brittle damage often occurs.
[0003] Adding fibers is a common means to solve the brittleness of geopolymers, and commonly used fibers include glass fibers, steel fibers, polypropylene fibers, polyoxymethylene fibers, and basalt fibers. However, glass fibers have high brittleness and poor weather resistance; steel fibers are prone to corrosion and have a large self-weight; polypropylene fibers have low tensile strength.
[0004] Basalt fibers have excellent high-temperature resistance, chemical corrosion resistance, and good mechanical properties, and their raw materials are abundant and the price is relatively low. However, since basalt fibers are mainly composed of chemical components such as SiO2, Al2O3, Fe2O3, and MgO that are prone to dissolution reactions with alkalis, this makes the surface and interior of basalt fibers easily eroded by alkali solutions in high-alkali environments such as geopolymers, resulting in a decrease in the mechanical properties and toughness of the fibers. Polyoxymethylene fibers have weak interfacial adhesion with the inorganic geopolymer matrix due to their high chemical inertness and are prone to debonding. In addition, the surfaces of both basalt fibers and polyoxymethylene fibers are smooth, and the interfacial bonding force with the geopolymer matrix is weak, which will affect their toughening effect in geopolymers. Summary of the Invention
[0005] This application proposes a preparation method of a geopolymer composite material based on modified fibers, including the following steps: S1: Fiber pretreatment, where the fiber is one of basalt fiber and polyoxymethylene fiber; S2: Surface roughening treatment of the fiber with a polyvinyl alcohol modified sizing agent to obtain roughened fiber; S3: Surface functional modification treatment of the roughened fiber with a functionalized modified sizing agent to prepare functionalized modified fiber; S4: Mix the powder and the expansion agent evenly by mass ratio, add an alkali activator solution and the functionalized modified fiber to prepare a geopolymer gel material; S5: Stir, mold, steam-cure, demold, and continue to cure the geopolymer gel material to obtain a geopolymer composite material based on modified fibers.
[0006] Among them, in step S1, the steps of fiber pretreatment include: S11: Immerse the fibers in the solution at a volume ratio of fiber / solution = 1 / 3. The solution is one of acetone solution or ethanol solution; S12: After soaking for 60 - 180 min, repeatedly rinse the fibers with deionized water; S13: Air-dry at a temperature of 25 - 40 °C.
[0007] Among them, in step S2, the steps of roughening the surface of the fibers with the polyvinyl alcohol modified sizing agent include: S21: Prepare a polyvinyl alcohol solution at a mass ratio of polyvinyl alcohol / deionized water = 1 / 25; S22: Perform a high-temperature water bath on the polyvinyl alcohol solution at a temperature above 95 °C and stir until the polyvinyl alcohol particles are completely dissolved to obtain the polyvinyl alcohol modified sizing agent; S23: Immerse the fibers in the polyvinyl alcohol modified sizing agent solution at a volume ratio of fiber / polyvinyl alcohol modified sizing agent = 1 / 3 for 5 - 10 min, and continuously stir during the immersion process; S24: Air-dry the immersed fibers at a temperature of 20 - 40 °C to obtain roughened fibers.
[0008] Among them, in step S3, the steps of preparing the functionalized modified sizing agent include: S31: Add nano-aluminum oxide to anhydrous ethanol in a certain mass ratio, add citric acid, heat and stir at a temperature of 50 - 70 °C, and obtain modified nano-aluminum oxide after filtration, washing and drying; S32: Add the modified nano-aluminum oxide to deionized water, stir to obtain a mixed solution, and add γ-aminopropyltrimethoxysilane to the mixed solution, and obtain the functionalized modified sizing agent after stirring evenly.
[0009] Among them, in step S3, the steps of surface functionalization modification of the roughened fibers with the functionalized modified sizing agent include: S33: Immerse the roughened fibers in the functionalized modified sizing agent at a volume ratio of roughened fiber / functionalized modified sizing agent = 1 / 3 for 5 - 10 min; S34: Perform air-drying at 20 - 40 °C, repeat the soaking and air-drying at least 2 times to obtain functionalized modified fibers.
[0010] Among them, the steps in step S4 include: S41: Crush and grind the coal gangue particles and slag, and obtain powder after screening; S42: Add a certain mass of alkali activator to water and stir until completely dissolved to obtain an alkali activator solution; S43: Stir and mix the powder and the expansive agent evenly to obtain a mixed dry powder, and add the mixed dry powder and the alkali activator solution into a stirring device; S44: During the low-speed stirring of the stirring device, add the functionalized modified fibers evenly. After low-speed stirring and high-speed stirring, a geopolymer gel material is prepared.
[0011] Among them, in step S4, the raw materials are in parts by mass and include 100 parts of powder, 21.0 - 23.0 parts of alkali activator, 1.8 - 2.4 parts of expansive agent, 3.0 - 3.5 parts of functionalized modified fibers, and 36.0 - 44.0 parts of water.
[0012] Among them, the alkali activator contains a water glass solution and a caustic alkali hydroxide, and the expansive agent is high-purity layered lithium saponite.
[0013] Among them, the water glass solution contains an alkali metal silicate, and the mass ratio of the alkali metal silicate to the solid of the caustic alkali hydroxide is 1:1. The total content of SiO2, MgO, and H2O in the lithium saponite is ≥85%.
[0014] This application also provides a geopolymer composite material based on modified fibers, and the geopolymer composite material based on modified fibers is prepared by the method of this application.
[0015] The preparation method of the geopolymer composite material based on modified fibers in this application uses functionalized modified fibers to form a gel geopolymer with industrial solid waste coal gangue and slag, and through alkali activation, a geopolymer composite material with high strength, excellent crack resistance and toughness is obtained, which promotes the high-value utilization of industrial solid waste and green sustainable development, and solves the problems of low toughness and high brittleness of geopolymer. Description of the Drawings
[0016] By reading the following detailed description with reference to the drawings, the above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become easy to understand. In the drawings, several embodiments of the present disclosure are shown in an exemplary rather than restrictive manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein: Figure 1 is a flow chart of the preparation method of the geopolymer composite material based on modified fibers in the embodiment of this application; Figure 2 is the SEM image (a) of the unmodified basalt fiber and the SEM image (b) of the modified basalt fiber in the embodiment of this application; Figure 3 is the SEM image (a) of the unmodified polyoxymethylene fiber and the SEM image (b) of the modified polyoxymethylene fiber in the embodiment of this application. Detailed Embodiments
[0017] Next, the technical solutions in the embodiments of the present disclosure will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative efforts belong to the scope of protection of the present disclosure.
[0018] The present application provides a method for preparing a geopolymer composite material based on modified fibers, comprising the following steps: S1: Fiber pretreatment, wherein the fiber is one of basalt fiber and polyoxymethylene fiber; Among them, the steps of the fiber pretreatment include: S11: Immerse the fiber in the solution according to the volume ratio of fiber / solution = 1 / 3, and the solution is one of acetone solution or ethanol solution; In this step, the concentration of the acetone solution is ≥80%, and the ethanol is an ethanol solution of 70-95%.
[0019] S12: After soaking for 60-180 min, repeatedly rinse the fiber with deionized water; The soaking time is preferably 120 min, and the number of times of repeatedly rinsing the fiber with deionized water is at least three times.
[0020] S13: Air-dry at a temperature of 25-40 °C.
[0021] The air-drying temperature is preferably 30 °C. In the actual air-drying process, the optimal temperature can be selected according to the processing environment, and no limitation is made here.
[0022] S2: Perform surface roughening treatment on the fiber with a polyvinyl alcohol modified sizing agent to obtain roughened fiber; The steps of performing surface roughening treatment on the fiber with the polyvinyl alcohol modified sizing agent include: S21: Prepare a polyvinyl alcohol solution according to the mass ratio of polyvinyl alcohol / deionized water = 1 / 25; S22: Perform a high-temperature water bath on the polyvinyl alcohol solution at a temperature greater than 95 °C and stir until the polyvinyl alcohol particles are completely dissolved to obtain a polyvinyl alcohol modified sizing agent; S23: According to the volume ratio of fiber / polyvinyl alcohol modified sizing agent = 1 / 3, immerse the fiber in the polyvinyl alcohol modified sizing agent solution for 5-10 min, and continuously stir during the immersion process; The stirring process in this step can be processed by a magnetic stirrer.
[0023] S24: Air-dry the soaked fiber at a temperature of 20-40 °C to obtain roughened fiber.
[0024] The roughened fiber is a fiber with a rough surface after being subjected to a surface roughening treatment.
[0025] S3: surface functionalization modification treatment of the roughened fiber is performed by using a functionalized modified sizing agent to prepare a functionalized modified fiber; The preparation steps of the functional modified wetting agent include: S31: adding nano-alumina to anhydrous ethanol in a certain mass ratio, adding citric acid, heating and stirring at a temperature of 50-70° C., filtering, washing, and drying to obtain modified nano-alumina; In this step, 2 g of nano-alumina can be added to 40 ml of anhydrous ethanol solution, 1.0 g of citric acid is added, and the mixture is stirred at 60° C. for 120 min, followed by filtration, washing, and drying to obtain modified nano-alumina.
[0026] It should be noted that the nano-alumina is a white powder with a particle size of 20-50 nm, a purity of ≥99%, a density of approximately 3.9 g / cm³, and a specific surface area of 150-250 m² / g; the purity of citric acid is ≥99%.
[0027] S32: adding modified nano-alumina to deionized water, stirring to obtain a mixed solution, adding γ-aminopropyltrimethoxysilane to the mixed solution, and stirring to obtain a functionalized modified wetting agent.
[0028] Add 2 g of modified nano-alumina particles to 60 ml of deionized water and stir at 300 r / min for 15-20 min. Add 1.5-2 g of γ-aminopropyltrimethoxysilane to the mixed solution and continue stirring for 15 min to form a uniform functionalized modified wetting agent.
[0029] The step of performing surface functional modification treatment on the roughened fiber by the functional modified sizing comprises: S33: Soak the roughened fiber in the functionalized modified sizing agent at a volume ratio of 1 / 3 for 5-10 minutes. S34: air-drying the fiber at 20-40° C., repeating the soaking and air-drying steps at least twice to obtain a functionalized modified fiber.
[0030] S4: mixing the powder and the expansion agent uniformly according to the mass ratio, adding the alkali activator solution and the functionalized modified fiber to prepare the geopolymer gel material; The specific steps include: S41: crushing and grinding the gangue particles and slag, and obtaining a powder after screening; The slag is grade S95 or above.
[0031] S42: Add a certain mass of alkali activator to water and stir until completely dissolved to obtain an alkali activator solution; S43: Stir and mix the powder and the expansive agent evenly to obtain a mixed dry powder, and add the mixed dry powder and the alkali activator solution to a stirring device; Here, the stirring device is a mixer, and the preferred stirring speed is 120 r / min, and the stirring time is 6 min.
[0032] S44: Uniformly add functionalized modified fibers during the low-speed stirring process of the stirring device. After low-speed stirring and high-speed stirring, a geopolymer gel material is prepared.
[0033] The low-speed stirring is controlled within 110 - 130 s, and after stopping stirring and scraping the wall, the high-speed stirring is not less than 90 s.
[0034] The raw materials are in parts by mass and include 100 parts of powder, 21.0 - 23.0 parts of alkali activator, 1.8 - 2.4 parts of expansive agent, 3.0 - 3.5 parts of functionalized modified fibers, and 36.0 - 44.0 parts of water, as shown in Table 1 specifically: Table 1: Raw materials and parts by mass
[0035] The alkali activator contains a water glass solution and caustic alkali hydroxide, and the expansive agent is high-purity layered lithium saponite.
[0036] Among them, the water glass solution contains alkali metal silicate, and the mass ratio of the alkali metal silicate to the solid of caustic alkali hydroxide is 1:1. Among them, the content of alkali metal silicate in the water glass solution is 35 - 41%, the modulus is 3.1 - 3.4, the mass fraction of alkali metal oxide is 9.0 - 12.0%, and the mass fraction of silicon dioxide is 25.0 - 30%; the purity of the caustic alkali hydroxide solid ≥ 85%. The total content of SiO2, MgO and H2O in the lithium saponite ≥ 85%.
[0037] S5: Stir, mold, steam-cure, demold, and continue to cure the geopolymer gel material to obtain a geopolymer composite material based on modified fibers.
[0038] Preferably, the steam-curing time is 24 h, the temperature for continuous curing is 15 - 25 °C, and the relative humidity ≥ 90%.
[0039] Through fiber modification, the corrosion resistance, degradation resistance and mineralization ability of the fiber can be improved. On the one hand, a protective layer is formed on the fiber surface to avoid being eroded; on the other hand, the surface roughness of the fiber can also be increased, and the mechanical interlock between the fiber and the matrix can be increased, thereby toughening the matrix.
[0040] The present invention realizes the high-value utilization of industrial solid waste residues, reduces carbon emissions. By using industrial solid waste residues such as coal gangue and slag as raw materials and combining with geopolymer cementitious technology, the high-value utilization of industrial waste residues is achieved, effectively reducing the dependence on natural resources. At the same time, the geopolymer technology abandons the dependence on traditional cement, avoiding a large amount of carbon emissions and energy consumption in the cement production process. In addition, natural clay mineral saponite generates hydrotalcite during the alkali activation process, enhancing the densification of the matrix material and inhibiting the shrinkage behavior of the geopolymer, thereby expanding the application scope and scenarios of geopolymer materials.
[0041] The present invention further improves the interfacial bonding force and material durability. The roughening treatment of the polyvinyl alcohol modified sizing agent not only increases the surface roughness of the fiber to enhance the mechanical interlocking between the fiber and the geopolymer matrix, but also provides a protective layer for the fiber to avoid the erosion of the external environment. For the surface functionalization modification treatment, on the one hand, the siloxy groups of the silane coupling agent γ-aminopropyltrimethoxysilane form stable siloxane bonds with the hydroxyl groups of the polyvinyl alcohol coating on the fiber surface, further enhancing the interfacial adhesion and alkali corrosion resistance; on the other hand, the nano-aluminum oxide particles are uniformly deposited on the surface of the polyvinyl alcohol coating through the functionalization modification treatment, further improving the mechanical interlocking effect between the fiber and the geopolymer matrix, and serving as nucleation sites for the hydration reaction to react with the silicon-oxygen and aluminum-oxygen tetrahedrons in the matrix through its high specific surface area to form silicon-aluminum oxides, effectively enhancing the interfacial bonding strength as chemical bonding. Through the synergistic enhancement effect of chemistry and physics, the present invention significantly improves the interfacial stability and bonding strength between basalt and polyoxymethylene fibers and geopolymer materials, and exhibits excellent corrosion resistance in an alkaline environment.
[0042] The present invention significantly improves the toughness and crack resistance of geopolymers. By using nano-aluminum oxide-polyvinyl alcohol functionalized modified fibers as toughening materials, through the formation of a flexible interface and enhanced interfacial bonding, the crack propagation mode in the geopolymer matrix is changed from a single shear mode to a tensile-shear mixed mode. This change significantly improves the initial fracture toughness and unstable fracture toughness of the composite material, effectively delaying the initiation and propagation of cracks, enhancing the crack resistance and ductility of the material, overcoming the inherent brittle defects of geopolymers, and making the composite material have higher safety and applicability in practical applications.
[0043] Example 1 This example is used to prepare a geopolymer composite material based on modified basalt fibers, including the following steps: S1: Pretreat the basalt fibers; S2: Carry out surface roughening treatment on the basalt fibers through a polyvinyl alcohol modified sizing agent to obtain roughened basalt fibers; S3: Carry out surface functionalization modification treatment on the roughened basalt fibers through a functionalized modified sizing agent to prepare functionalized modified basalt fibers; Specifically, it includes: adding 0.2 kg of nano-aluminum oxide into 4 L of anhydrous ethanol solution, adding 0.1 kg of citric acid, stirring at 60 °C for 2 h, then filtering, washing and drying to obtain modified nano-aluminum oxide; adding 0.2 kg of modified nano-aluminum oxide particles into 6 L of deionized water and stirring at 300 r / min for 18 min; adding 0.175 kg of γ-aminopropyltrimethoxysilane into the mixed solution and continuing to stir for 15 min to form a uniform functionalized modified sizing agent; performing surface functionalized modification treatment on the roughened basalt fiber in S3 through the functionalized modified sizing agent to prepare functionalized modified basalt fiber.
[0044] S4: Mix the powder and the expansive agent evenly by mass ratio, add the alkali activator solution and the functionalized modified fiber to obtain a geopolymer gel material.
[0045] Specifically, the following raw materials are weighed according to the ratio: 30.0 kg of coal gangue powder, 70.0 kg of slag powder, 2.1 kg of laponite, 16.0 kg of water glass solution, 6.0 kg of sodium hydroxide solid, 3.2 kg of functionalized modified basalt fiber, and 40.0 kg of water; crush and grind the coal gangue particles, sieve the coal gangue powder of 140 - 200 mesh to obtain coal gangue powder; pour the weighed alkali activator into water and stir until completely dissolved to obtain an alkali activator solution; pour the weighed powder components and the expansive agent into a mixer and dry stir at 120 r / min for ≥3 min to make the powder evenly mixed to obtain a mixed dry powder; pour the mixed dry powder and the alkali activator solution into a stirring pot, add the functionalized modified basalt fiber evenly while stirring at a low speed, control the low-speed stirring for 110 - 130 s, stop stirring and scrape the wall, then stir at a high speed for not less than 90 s, and the whole process does not exceed 300 s to obtain a functionalized modified basalt fiber-reinforced geopolymer gel material.
[0046] S5: Stir, mold, steam cure, demold, and continue to cure the geopolymer gel material to obtain a geopolymer composite material based on the modified fiber.
[0047] Example 2 This example is used to prepare a geopolymer composite material based on modified polyoxymethylene fiber.
[0048] This example has the same steps as Example 1 for preparing a geopolymer composite material based on modified fiber, except that the fiber used is polyoxymethylene fiber, and the raw materials and ratios are as follows: 30.0 kg of coal gangue powder, 70.0 kg of slag powder, 2.1 kg of laponite, 16.0 kg of water glass solution, 6.0 kg of sodium hydroxide solid, 3.35 kg of functionalized modified polyoxymethylene fiber, and 40.0 kg of water.
[0049] Comparative Example 1 This comparative example is used to prepare a geopolymer composite material without fibers.
[0050] Weigh the following raw materials according to the ratio: 30.0 kg of coal gangue powder, 70.0 kg of slag powder, 2.1 kg of saponite, 16.0 kg of water glass solution, 6.0 kg of solid sodium hydroxide, and 40.0 kg of water; Crush and grind the coal gangue particles, and screen the coal gangue powder with a mesh size of 140 - 200 to obtain coal gangue powder; Pour the weighed alkali activator into water and stir until completely dissolved to obtain an alkali activator solution; Pour the weighed powder components and the expansion agent into a mixer, and dry - stir at 120 r / min for ≥3 min to make the powder components evenly mixed to obtain a mixed dry powder; Pour the mixed dry powder and the alkali activator solution into a stirring pot, stir at a low speed, control the low - speed stirring for 110 - 130 s, stop stirring and scrape the wall, then stir at a high speed for not less than 90 s, and the whole process does not exceed 300 s to prepare a geopolymer gel material; Mix, mold, steam - cure, demold, and continue to cure the geopolymer gel material to obtain the product.
[0051] Comparative Example 2 This comparative example is used to prepare a geopolymer composite material containing basalt fibers.
[0052] Weigh the following raw materials according to the ratio: 30.0 kg of coal gangue powder, 70.0 kg of slag powder, 2.1 kg of saponite, 16.0 kg of water glass solution, 6.0 kg of solid sodium hydroxide, 3.2 kg of basalt fibers, and 40.0 kg of water; Crush and grind the coal gangue particles, and screen the coal gangue powder with a mesh size of 140 - 200 to obtain coal gangue powder; Pour the weighed alkali activator into water and stir until completely dissolved to obtain an alkali activator solution; Pour the weighed powder components and the expansion agent into a mixer, and dry - stir at 120 r / min for ≥3 min to make the powder components evenly mixed to obtain a mixed dry powder; Pour the mixed dry powder and the alkali activator solution into a stirring pot, add basalt fibers evenly while stirring at a low speed, control the low - speed stirring for 110 - 130 s, stop stirring and scrape the wall, then stir at a high speed for not less than 90 s, and the whole process does not exceed 300 s to prepare a basalt - fiber - reinforced geopolymer gel material; Mix, mold, steam - cure, demold, and continue to cure the basalt - fiber - reinforced geopolymer gel material to obtain the product.
[0053] Comparative Example 3 This comparative example is used to prepare a geopolymer composite containing polyoxymethylene fibers.
[0054] Weigh the following raw materials according to the ratio: 30.0 kg of coal gangue powder, 70.0 kg of slag powder, 2.1 kg of laponite, 16.0 kg of water glass solution, 6.0 kg of solid sodium hydroxide, 3.35 kg of polyoxymethylene fibers, and 40.0 kg of water; Crush and grind the coal gangue particles, and sieve the coal gangue powder with 140 - 200 meshes to obtain the coal gangue powder; Pour the weighed alkali activator into water and stir until completely dissolved to obtain the alkali activator solution; Pour the weighed powder components and the expansion agent into a mixer, and dry - stir at 120 r / min for ≥3 min to make the powder evenly mixed to obtain the mixed dry powder; Pour the mixed dry powder and the alkali activator solution into a stirring pot, and while stirring at a low speed, evenly add the polyoxymethylene fibers. The low - speed stirring is controlled for 110 - 130 s. After stopping the stirring and scraping the wall, stir at a high speed for no less than 90 s. The whole process shall not exceed 300 s to prepare the polyoxymethylene fiber - reinforced geopolymer gel material; Mix, mold, steam - cure, demold, and continue to cure the polyoxymethylene fiber - reinforced geopolymer gel material to obtain the product.
[0055] Perform mechanical property tests and fracture toughness tests on the specimens prepared in Examples 1 - 2 and Comparative Examples 1 - 3 respectively. The test results are shown in Tables 2 and 3: Table 2 Mechanical strength properties of different examples of the present invention
[0056] Table 3 Fracture toughness of different examples of the present invention
[0057] Compared with Comparative Example 1, the geopolymer materials of Examples 1 - 2 and Comparative Examples 2 - 3 show a significant strength improvement. Among them, the 28 - day compressive strength of Example 2 reaches 47.51 MPa, which is about 55.4% higher than that of Comparative Example 1. Example 1 also shows excellent performance, with a 28 - day compressive strength of 36.16 MPa, far exceeding 30.58 MPa of Comparative Example 1. As Figure 2 and Figure 3As shown, after the basalt and polyoxymethylene fibers are modified, the surface roughness increases significantly, improving the mechanical interlock between the fibers and the geopolymer matrix, effectively increasing the restraint on the matrix, enhancing the ductility of the geopolymer material, and thus improving the brittle fracture defect. At the same time, the surface modification coating isolates the alkaline erosion of the basalt fibers by the high-alkali environment of the geopolymer, avoids the performance degradation caused by fiber corrosion, and increases the durability of the fibers. The enhanced mechanical interlock, interfacial adhesion, and bonding strength all contribute to improving the interfacial strength between the fibers and the geopolymer matrix, thereby increasing the compressive and flexural strengths of the geopolymer.
[0058] Compared with Comparative Example 1, Examples 1-2 exhibit better toughness. The performance of Example 1 is also better than that of Comparative Example 2, with the instability toughness at 28 days increased by about 9.4%. The crack initiation toughness of Example 2 reaches 0.49 MPa·m¹ / ², which is 58.1% higher than that of Comparative Example 3, and the instability toughness is also increased to 5.86 MPa·m¹ / ². The improvement in fracture toughness is due to two reasons. On the one hand, the surface of the unmodified fibers is smooth, with weak interfacial bonding force, making it difficult to effectively disperse cracks. The roughening treatment and functional modification improve the surface characteristics, enhancing the adhesion and mechanical interlock between the fibers and the matrix. On the other hand, the modified fibers form a flexible interface in the matrix, changing the crack propagation mode from a single shear mode to a tensile-shear mixed mode, effectively dispersing stress, significantly enhancing the crack initiation toughness and unstable fracture toughness of the geopolymer, and delaying the crack initiation and propagation process.
[0059] From Examples 1-2 and Comparative Examples 2-3, it can be found that the present invention uses the nano-alumina-polyvinyl alcohol functional modification technology to functionally modify different fibers and applies the functionally modified fibers as reinforcement materials to geopolymers. The experimental results show a significant improvement in the toughness and brittleness of the functionally modified fibers compared to the unmodified fibers in geopolymers, indicating that the nano-alumina-polyvinyl alcohol functional modification technology proposed in the present invention is applicable to the modification of various fibers and has broad application potential in the field of fiber-reinforced geopolymers.
[0060] The present invention uses the nano-alumina-polyvinyl alcohol functional modification technology to functionally modify the surface of fibers, preparing toughening fibers suitable for geopolymers, which have broader application potential. Using industrial solid waste coal gangue and slag as raw materials to prepare a functionally modified fiber-reinforced geopolymer cementitious material, it has excellent mechanical properties and fracture toughness: the functional modification treatment increases the chemical and mechanical adhesion between the fibers and the geopolymer matrix, enhances the bridging effect of the fiber-geopolymer matrix, helps reduce shrinkage cracking in the interfacial transition zone, disperse stress concentration, prevent the expansion and extension of cracks, and significantly improve the fracture toughness of the material.
[0061] Although the preferred embodiments of the embodiments of the present application have been described, those skilled in the art can make additional changes and modifications to these embodiments once they learn the basic creative concepts. Therefore, the appended claims are intended to be construed as including the preferred embodiments as well as all changes and modifications that fall within the scope of the embodiments of the present application.
[0062] Finally, it should also be noted that in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or terminal device comprising a series of elements not only includes those elements but also includes other elements not expressly listed, or further includes elements inherent to such process, method, article or terminal device. Without further limitation, an element defined by the statement "comprising an..." does not exclude the presence of additional identical elements in the process, method, article comprising the element.
[0063] Specific examples are used in this application to illustrate the principles and implementation manners of the present application. The description of the above embodiments is only for helping to understand the method and its core idea of the present application; at the same time, for those of ordinary skill in the art, according to the idea of the present application, there will be changes in the specific implementation manners and application scopes. In summary, the content of this specification should not be construed as a limitation to the present application.
Claims
1. A preparation method of a geopolymer composite based on modified fibers, characterized in that, It includes the following steps: S1: Fiber pretreatment, where the fiber is one of basalt fiber and polyoxymethylene fiber; S2: Surface roughening treatment of the fiber with a polyvinyl alcohol modified sizing agent to obtain roughened fiber; S3: Surface functional modification treatment of the roughened fiber with a functionalized modified sizing agent to prepare functionalized modified fiber; S4: Mix the powder and the expansive agent evenly by mass ratio, add the alkali activator solution and the functionalized modified fiber to obtain a geopolymer gel material; S5: Stir, mold, steam cure, demold, and continue to cure the geopolymer gel material to obtain a geopolymer composite based on the modified fiber.
2. The preparation method of the geopolymer composite material based on modified fibers according to claim 1, characterized in that, In step S1, the steps of the fiber pretreatment include: S11: Immerse the fiber in the solution at a volume ratio of fiber / solution = 1 / 3, where the solution is one of acetone solution or ethanol solution; S12: After soaking for 60 - 180 min, repeatedly rinse the fiber with deionized water; S13: Air dry at a temperature of 25 - 40°C.
3. The preparation method of the geopolymer composite material based on modified fibers according to claim 1, characterized in that, In step S2, the steps of the surface roughening treatment of the fiber with the polyvinyl alcohol modified sizing agent include: S21: Prepare a polyvinyl alcohol solution at a mass ratio of polyvinyl alcohol / deionized water = 1 / 25; S22: Perform a high-temperature water bath on the polyvinyl alcohol solution at a temperature greater than 95°C and stir until the polyvinyl alcohol particles are completely dissolved to obtain a polyvinyl alcohol modified sizing agent; S23: Immerse the fiber in the polyvinyl alcohol modified sizing agent solution at a volume ratio of fiber / polyvinyl alcohol modified sizing agent = 1 / 3 for 5 - 10 min, and continuously stir during the immersion process; S24: Air dry the immersed fiber at a temperature of 20 - 40°C to obtain roughened fiber.
4. The preparation method of the geopolymer composite material based on modified fibers according to claim 1, characterized in that, In step S3, the preparation steps of the functionalized modified sizing agent include: S31: Add nano-aluminum oxide to anhydrous ethanol at a certain mass ratio, add citric acid, heat and stir at a temperature of 50 - 70°C, and obtain modified nano-aluminum oxide after filtration, washing, and drying; S32: Add the modified nano-aluminum oxide to deionized water, stir to obtain a mixed solution, and add γ-aminopropyltrimethoxysilane to the mixed solution, and stir evenly to obtain a functionalized modified sizing agent.
5. The preparation method of the geopolymer composite material based on modified fibers according to claim 4, characterized in that, In step S3, the steps of the surface functional modification treatment of the roughened fiber with the functionalized modified sizing agent include: S33: Immerse the roughened fiber in the functionalized modified sizing agent at a volume ratio of roughened fiber / functionalized modified sizing agent = 1 / 3 for 5 - 10 min; S34: Perform air drying at 20 - 40°C, repeat the immersion and air drying at least 2 times to obtain functionalized modified fiber.
6. The preparation method of the geopolymer composite material based on modified fibers according to claim 1, characterized in that, The steps in step S4 include: S41: Grind and screen the coal gangue particles and slag to obtain a powder; S42: Add a certain mass of alkali activator to water and stir until completely dissolved to obtain an alkali activator solution; S43: Stir and mix the powder and the expansive agent evenly to obtain a mixed dry powder, and add the mixed dry powder and the alkali activator solution to a stirring device; S44: During the low-speed stirring of the stirring device, the functionalized modified fibers are uniformly added. After low-speed stirring and high-speed stirring, the geopolymer gel material is prepared.
7. The preparation method of the geopolymer composite material based on modified fibers according to claim 6, wherein, In step S4, the raw materials include 100 parts by mass of powder, 21.0 - 23.0 parts of alkali activator, 1.8 - 2.4 parts of expansive agent, 3.0 - 3.5 parts of functionalized modified fibers, and 36.0 - 44.0 parts of water.
8. The preparation method of the geopolymer composite material based on modified fibers according to claim 6, characterized in that, The alkali activator contains a water glass solution and caustic alkali hydroxide, and the expansive agent is high-purity layered hectorite.
9. The preparation method of the geopolymer composite material based on modified fibers according to claim 8, characterized in that, The water glass solution contains alkali metal silicate, and the mass ratio of the alkali metal silicate to the solid of caustic alkali hydroxide is 1:
1. The total content of SiO2, MgO, and H2O in the hectorite is ≥85%.
10. A geopolymer composite based on modified fibers, characterized in that, The geopolymer composite material based on modified fibers is prepared by any of the methods in claims 1 - 9.
Citation Information
Cited By
Nanometer material modified geopolymer-based self-compacting concrete and construction process
CN120887690A
Geopolymer grouting material as well as preparation method and application thereof
CN121405401A
Fiber-reinforced high-performance geopolymer concrete and preparation method thereof
CN122355629A
Fiber reinforced high performance polymer concrete and method of making same
CN122355629B